2018
DOI: 10.1002/jbmr.3550
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D and Intact Parathyroid Hormone Influence Muscle Outcomes in Children and Adolescents

Abstract: Increases in 25-hydroxyvitamin D concentrations are shown to improve muscle strength in adults; however, data in pediatric populations are scant and equivocal. In this ancillary study of a larger-scale, multi-sited, double-blind, randomized, placebo-controlled vitamin D intervention in US children and adolescents, we examined the associations between changes in vitamin D metabolites and changes in muscle mass, strength, and composition following 12-weeks of vitamin D3 supplementation. Healthy male and female, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…One of the studies included in this review (22) presented data that considered the subjects' skin color and gender. In this study, white girls had higher levels of circulating 25OHD (80.5 ± 6.1 nmol/L) than black girls (58.9 ± 18.2 nmol/L) and white and black boys (79.8±3.0 nmol/L and 62.0±15.2 nmol/L, respectively).…”
Section: ' Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the studies included in this review (22) presented data that considered the subjects' skin color and gender. In this study, white girls had higher levels of circulating 25OHD (80.5 ± 6.1 nmol/L) than black girls (58.9 ± 18.2 nmol/L) and white and black boys (79.8±3.0 nmol/L and 62.0±15.2 nmol/L, respectively).…”
Section: ' Discussionmentioning
confidence: 99%
“…The age range was 5-11 years. Three studies were identified with insufficient classification of vitamin D levels (22)(23)(24), and two studies (25,26) included subjects with deficient vitamin D levels as defined by the International Life Science Institute of Brazil (27). The characteristics of the included studies are listed in Table 1.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…When the concentration of 25(OH)D is higher than 32 ng/ml, the prevalence of cardiac metabolic risk in children will be reduced by 49% [36]. It has been found that increasing circulating 25(OH)D concentration can reduce the fat tissue (IMAT) between forearm muscles and increase the cross-sectional area (MCSA) of forearm and calf skeletal muscles [37], which may improve the contractility of lower limb muscles in OI children and avoid re ex hypotension due to upright.…”
Section: Discussionmentioning
confidence: 99%
“…When the concentration of 25(OH)D is higher than 32 ng/ml, the prevalence of cardiac metabolic risk in children will be reduced by 49% [36]. It has been found that increasing circulating 25(OH)D concentration can reduce the fat tissue (IMAT) between forearm muscles and increase the cross-sectional area (MCSA) of forearm and calf skeletal muscles [37], which may improve the contractility of lower limb muscles in OI children and avoid re ex hypotension due to upright. Chaudhari reported a case of 1-hydroxylase de cient POTS patients with improved palpitation symptoms after oral vitamin D treatment, suggesting that this kind of patients can be treated with calcitriol [38], but this still needs larger sample clinical trials to verify.…”
Section: Discussionmentioning
confidence: 99%